2014
DOI: 10.15448/1980-8623.2014.1.12243
|View full text |Cite
|
Sign up to set email alerts
|

Valores Humanos e Significado do Dinheiro: Um Estudo Correlacional

Abstract: RESUMO Este estudo teve por objetivo verificar a relação entre os valores humanos e o significado do dinheiro para crianças. Participaram 1.445 estudantes com idade média de 11 anos (dp = 1,09), a maioria do sexo masculino (51%), distribuídos entre as regiões Norte (n = 585) e Nordeste (n = 860) do Brasil. Estes responderam a Escala de Significado do Dinheiro para Crianças (ESDC), Questionário de Valores Básicos Infantis (QVBI) e questões demográficas. Os resultados indicaram diferenças com relação à variável … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Regarding the investigation of the effects of money on people's decisionmaking, our results suggest that money may be a determinant variable, at least in the Brazilian population. This data is in line with the current literature, as it points out that throughout history, money has played a relevant role in the lives of individuals and societies (Lauer-Leite et al, 2014). It is also indicated that money can be considered a guiding principle used by individuals as a criterion to justify their actions (Lins & Poeschl, 2015) and that through purchasing power, and thus, money, there is a materialization of decision-making power (Silva & Henriques, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding the investigation of the effects of money on people's decisionmaking, our results suggest that money may be a determinant variable, at least in the Brazilian population. This data is in line with the current literature, as it points out that throughout history, money has played a relevant role in the lives of individuals and societies (Lauer-Leite et al, 2014). It is also indicated that money can be considered a guiding principle used by individuals as a criterion to justify their actions (Lins & Poeschl, 2015) and that through purchasing power, and thus, money, there is a materialization of decision-making power (Silva & Henriques, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…It is also indicated that money can be considered a guiding principle used by individuals as a criterion to justify their actions (Lins & Poeschl, 2015) and that through purchasing power, and thus, money, there is a materialization of decision-making power (Silva & Henriques, 2017). One possible explanation suggests that money can be considered an instrument to mediate the satisfaction of human needs (Lauer-Leite et al, 2014), having an extraordinarily large rewarding potential (Skinner, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…These perceptions match the meaning attributed to money throughout history. According to Lauer-Leite 9 , money has taken on a key role within the lives of people, institutions and countries, "especially as it is an instrument for mediation that makes it possible to meet human needs, as well as technological, economic and social development". The classic idea that time is money is still present nowadays.…”
Section: Money Does Not Bring Happinessmentioning
confidence: 99%